Journey to vaccination using a heuristic approach in Pakistan: a qualitative study - Tabassum, Farhana; ., Nazia; ., Tooba; Nooruddin, Shanila; Hussain, Imtiaz; Umer, Muhammad; Feroz, Khaild; Aarif, Shabina; Soofi, Sajid; Habib, Atif (International Journal Of Community Medicine And Public Health, 2022)
Background: Immunization has significant health benefits particularly for children. Despite the rigorous efforts, immunization coverage in Pakistan has stagnated over the last decade. Methods: 42 in-depth interviews (IDIs) were conducted in polio high-risk areas of Pakistan involving mothers, fathers, polio workers and vaccinators to identify influencing and non-influencing factors that serve as a cue to action for childhood immunization using the heuristic approach contributing to journey to vaccination. Results: Participants shared different underlying fears and psychosocial factors concerning vaccines such as painful neonatal experiences, doubts, fear of vaccine-related side effects, distrust, treatment, morbidity and mortality of their children. Parents in favour of vaccinating their children, when afflicted with traumatic experiences, skipped vaccines for the time being. When counselled by the health-care providers they started vaccination again. While refusal parents were very rigid and after witnessing any harrowing vaccine-related experience, their decision not to vaccinate became stronger. Conclusions: Vaccination uptake is significantly influenced by vaccine-related traumatic life experiences which need to be explored and addressed timely as vaccine-hesitancy can become a more serious threat to global health.